Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/molecules25194483
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Beebread Caviar from Buckwheat Honey through Immobilization with Sodium Alginate

Abstract: Honeys have a pleasant taste and a wide range of use. They are characterized by a relatively high consumption compared to bee pollen or beebread. Honeys are the most popular bee products. Considering health reasons, beebread exhibits the strongest properties as it has the highest nutritional value as well as strong detoxifying, antioxidant, and antiradical properties. Despite having such valuable properties, consumption of beebread is negligible; sometimes, it is limited only to supplementation in case of dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The mixture of sturgeon DNA samples served as a positive control. Ten animal and plant DNA samples (salmon, trout, herring, cod, snail, honey, pectin, soybean, kelp, and buckwheat) [ 9 , 10 ] were amplified to verify the specificity of primer sets II and III. The results showed that the two self-designed primer sets had no obvious nonspecific amplification in all the DNA samples except sturgeon ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mixture of sturgeon DNA samples served as a positive control. Ten animal and plant DNA samples (salmon, trout, herring, cod, snail, honey, pectin, soybean, kelp, and buckwheat) [ 9 , 10 ] were amplified to verify the specificity of primer sets II and III. The results showed that the two self-designed primer sets had no obvious nonspecific amplification in all the DNA samples except sturgeon ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Caviar imitations are made from marine fish, lobster meat mixed with seaweed, etc., as well as from plant materials (pectin, honey and buckwheat, soybean meal, kelp, etc.) with food additives such as pigment, essence, and salt, which imitate the appearance and taste of natural caviar [ 9 , 10 ]. The nutritional composition of natural caviar and the caviar substitutes varies significantly among different species.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the mixture of bee pollen, bee salivary enzymes, and regurgitated honey fermented by indigenous microbes is another bee product, which is colloquially called beebread ( Mohammad et al, 2021 ). Smuga-Kogut et al invented a unique buckwheat honey beebread caviar (collected in Stonio Apiary, West Pomerania, Poland) through immobilization with sodium alginate ( Smuga-Kogut et al, 2020 ). The beebread originated from the Jeyce apiary, comprising 180 bee colonies near a buckwheat crop (Darlowo, West Pomerania, Poland).…”
Section: Alginate-based Nanomaterials For Biomedical and Pharmaceutic...mentioning
confidence: 99%
“…Because beebread includes a high lactic acid concentration, beebread caviar may also be categorized as a probiotic food. This novel, appealing and easy method of beebread ingestion in the shape of the caviar might become one of the products of pleasant and valuable cuisine ( Smuga-Kogut et al, 2020 ).…”
Section: Alginate-based Nanomaterials For Biomedical and Pharmaceutic...mentioning
confidence: 99%